Financial Climate‐Risk Measurement, Impact Funds, and Green Transitions - LAUX, VOLKER; MAHIEUX, LUCAS (Journal of Accounting Research, 2026)
ABSTRACT Regulators are contemplating or mandating precise measurement of financial climate‐risk exposure to promote sustainable investments. We show that such mandates can be counterproductive in the presence of social funds that catalyze change by subsidizing the adoption of cleaner production technologies. Firms can exploit a social fund's impact motive by measuring their climate‐risk exposure imprecisely. This strategic imprecision prevents the fund from distinguishing between firms that require subsidies and those that would switch to clean technologies for financial reasons alone, thereby increasing the ex ante subsidies firms can extract. A by‐product of this rent‐seeking behavior is that firms adopt clean technologies more frequently than would be jointly efficient under precise measurement. Our analysis suggests that the regulatory push for precise climate‐risk measurement can reduce social funds' impact and the frequency of green transitions.